2008
DOI: 10.1177/1559827608327916
|View full text |Cite
|
Sign up to set email alerts
|

Modern Management of the Migraine Headache

Abstract: Migraine headache is a debilitating disorder that affects millions of people in the United States and worldwide. The diagnosis of migraine can significantly affect quality of life, health care costs, and daily productivity. Hundreds of trials and many guidelines have documented various approaches to migraine management, whether via acute treatment or chronic migraine prophylaxis. Acute or abortive migraine management encompasses specific and nonspecific migraine therapeutics, including nonopioid and opioid ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Pharmacological treatments are common, with both abortive and prophylactic medications used; however, these medications are burdened by side effects and cost. 5 Non-pharmacological interventions, such as behavioral therapy, 6 relaxation therapy, and cognitive behavioral therapy, have also been employed, with varying degrees of success. 5 Despite the variety of treatment approaches available, migraineurs report that they feel their treatment is insufficient or unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological treatments are common, with both abortive and prophylactic medications used; however, these medications are burdened by side effects and cost. 5 Non-pharmacological interventions, such as behavioral therapy, 6 relaxation therapy, and cognitive behavioral therapy, have also been employed, with varying degrees of success. 5 Despite the variety of treatment approaches available, migraineurs report that they feel their treatment is insufficient or unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…A recent Cochrane review on acupuncture has reported that it is effective and could be considered a treatment option for migraine prophylaxis [17]. Other nonpharmacological alternatives (i.e., transcutaneous electrical nerve stimulation, cervical manipulation and hypnosis) have insufficient evidence to be recommended as approaches for migraine treatment [16]. With regard to the pharmacologic approach, there are only a few clinical trials evaluating drug treatment of migraine during pregnancy.…”
Section: Migraine Management In Pregnancymentioning
confidence: 99%
“…Drug therapy during the first 12 weeks after conception is, moreover, particularly challenging because the fetus is most vulnerable to a possible teratogenic factor as most organ development occurs during this period [15]. Non-pharmacological approaches (i.e., acupuncture, relaxation training, thermal or electromyographic biofeedback, and cognitive behavioral therapy) with reported evidence of efficacy [16,17] can be used in disease management. A recent Cochrane review on acupuncture has reported that it is effective and could be considered a treatment option for migraine prophylaxis [17].…”
Section: Migraine Management In Pregnancymentioning
confidence: 99%
“…Opiates, benzodiazpines, and triptans are commonly employed as rescue medications for migraines, but these medications are burdened by side effects and risks such as medication-overuse headaches, abuse, and addiction. 5 Prophylactic medications used in the treatment of migraine headaches tend to fall into the categories of antidepressants, anticonvulsants, and beta-blockers. 6 Similar to abortive medications, prophylactic medications can carry serious side effects that can interfere with patients’ daily lives.…”
Section: Introductionmentioning
confidence: 99%